ENTREPRENEURIAL KNOWLEDGE, ENTREPRENEURIAL INTENTION, DAN ENTREPRENEURIAL ORIENTATION PADA PENDIDIKAN ILMU AKUNTANSI - Tanjaya, Clarisia; Radianto, Wirawan ED (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
This study aims to prove whether there are differences in entrepreneurialknowledge, entrepreneurial intention, and entrepreneurial orientationin accounting students in higher education. The problem with this researchis whether there are differences in entrepreneurial knowledge, entrepreneurialintention, and entrepreneurial orientation between junior studentsand senior students. This research used quantitative analysis and surveymethod is applied to gather information. Then analyze the data usingthe independent sample T test. The results of this study are there are differencesin entrepreneurial knowledge, entrepreneurial intention, and entrepreneurialorientation between junior and senior accounting students.